2017
DOI: 10.1039/c7ta02283b
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and durable nitrogen doped-reduced graphene oxide/double perovskite bifunctional hybrid catalysts

Abstract: A-site cation doping in perovskite-based materials (ABO3 formula) has a significant effect on the bifunctional oxygen activity of the electrocatalysts with chemical stability, enabling the design of highly active, durable, and cost-effective catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…The deconvolution of O 1s peaks (Figure a) shows more than one type of oxygen species. The peaks of O 1s are complex and can be resolved into two main components: the lower binding energy peak at 528.7 eV can be attributed to lattice oxygen, such as Nd–O and Ni–O in the epitaxial NNO films, while the binding energy peak at ≈531.1 eV is considered to be highly oxidative oxygen species (O 2 2− /O − ) and hydroxyl groups (OH − ), which are closely related with Vo . Although it is technically difficult to acquire the exact stoichiometry of NNO film, the quantitative understanding about the tendency of V O and valence states of Ni ions can be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The deconvolution of O 1s peaks (Figure a) shows more than one type of oxygen species. The peaks of O 1s are complex and can be resolved into two main components: the lower binding energy peak at 528.7 eV can be attributed to lattice oxygen, such as Nd–O and Ni–O in the epitaxial NNO films, while the binding energy peak at ≈531.1 eV is considered to be highly oxidative oxygen species (O 2 2− /O − ) and hydroxyl groups (OH − ), which are closely related with Vo . Although it is technically difficult to acquire the exact stoichiometry of NNO film, the quantitative understanding about the tendency of V O and valence states of Ni ions can be determined.…”
Section: Resultsmentioning
confidence: 99%
“…BFO showed a larger crystallite size of 4.99 nm, compared to that of the doped BFO materials. Bi 0.6 Ba 0.4 FeO 3 (BBFO), Bi 0.6 Sr 0.4 FeO 3 To better understand the nature of the detailed structural information of BFO-based materials, the XRD patterns of overall catalysts were further analyzed by the Rietveld renement using the Fullprof program, 51 and Fig. 1(b) shows the renement results.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers reported that the surface oxidation and amorphization of oxide and agglomeration of nanoparticles are responsible as the main degradation mechanisms of OER and ORR activities during the long-term electrochemical reactions associated with oxygen. 21,51,[69][70][71] 3.3 Thermomechanical and electrical properties of BFO and BCFO at high temperature A major technical challenge in SOFC research is to develop cathode materials of similar thermal expansion coefficient (TEC) to those of other cell components (anode, electrolyte, and contact functional layers) to mitigate thermomechanical stresses, especially during thermal cycling. 7,39,[72][73][74][75] The TEC (a TEC ) commonly describes how a compound changes unit cell parameter in response to temperature, and is dened as;…”
Section: Electrocatalytic Activity and Stability Of The Bfo-based Catmentioning
confidence: 99%
“…Coupling perovskites with carbon can help overcome their intrinsic shortage of the electrical conductivity, resulting in enhanced electrochemical performance . For instance, the Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (BSCF) modified with acetylene black (BSCF/AB) exhibited significantly higher ORR/OER activity than the pristine BSCF catalyst (Figure d), which is attributed to the enhanced electrical conductivity and the altered oxidation state of Co by carbon .…”
Section: Carbon‐based Compositesmentioning
confidence: 99%